1981
DOI: 10.1007/bf01721056
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of hypocholesterolemia in hospitalized patients

Abstract: Hypocholesterolemia (less than 120 mg/dl) was found in 200 out of 3,700 patients admitted consecutively to a University Department of Internal Medicine. In 91, hypocholesterolemia as defined above could be confirmed in a second serum sample on the following day. Mortality during hospitalization in this group was 32%. When diagnoses were grouped into 5 categories, prognosis was particularly poor in heart (36%) and liver disease (31%) and in malignancies (33%), while patients with malabsorption syndromes had a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

1983
1983
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 16 publications
2
20
0
1
Order By: Relevance
“…Low serum albumin concentration, hypocholesterolaemia and anaemia are all indicators of risk for death in hospitalized and longterm care patients [61][62][63][64][65]. They might be markers for severe disease [66], although increased risk also occurs in older people at home [64,[67][68][69]. Poor nutrition also correlates with measures of health care utilization such as length of hospital stay [60,63,70].…”
Section: Consequences Of Nutritional Disorders In Late Lifementioning
confidence: 99%
“…Low serum albumin concentration, hypocholesterolaemia and anaemia are all indicators of risk for death in hospitalized and longterm care patients [61][62][63][64][65]. They might be markers for severe disease [66], although increased risk also occurs in older people at home [64,[67][68][69]. Poor nutrition also correlates with measures of health care utilization such as length of hospital stay [60,63,70].…”
Section: Consequences Of Nutritional Disorders In Late Lifementioning
confidence: 99%
“…Total cholesterol levels, in contrast, are normal to low [2,4]. Hypertriglyceridemia has been associated with athero sclerosis in certain populations [5,6], and hypocholesterolemia has been associated with chronic wasting diseases [7,8]. Since serum triglyceride (TG) and cholesterol levels were two of the variables used in subject classification, this study was undertaken to determine if these variables remained stable over time on dialysis.…”
mentioning
confidence: 99%
“…However, the effects of cytokines on lipoprotein metabolism are complex [17], and the mechanisms leading to low cholesterol concentration have not been studied in detail. trauma might be attributed to temporary liver malfunction [24]. In vitro studies in HepG2 cells (which serve as a model for liver cells) have shown that TNF-a, Il-1 and Il-6 decrease the accumulation of apo-A1 and apo-B and lecithin: cholesterol acyltransferase, and also decrease expression of m-RNA for apo-A1 [25].…”
Section: Discussionmentioning
confidence: 98%